Ecological Zonation As A Tool For Restoration Of Degraded Forests In Northern Mongolia - Antonín Kusbach; Tadeáš Štěrba; Jan Šebesta; Tomáš Mikita; Enkhtuya Bazarradnaa; Sarantuya Dambadarjaa; Martin Smola (Geography, Environment, Sustainability)
We developed a geo-vegetation zonation in the Khaan Khentii massif, northern Mongolia. Our specific objective was to assess and classify the response of the tree vegetation to environmental factors operating at a coarse climatic level. We sampled forest ecosystem vegetation, climate, physiographic features, and soil properties. Our analysis included clustering, ordination, classification, and ANOVA techniques. Based on the complex data set, we identified three geo-vegetation zones: forest-steppe, montane and dark taiga zone. We characterized them based on the regional environmental factors; (1) climate as indicated by altitude, i.e., precipitation, (2) geomorphology by an index of the vertical distance to channel network and soils by O horizon thickness and soil types. Birch and aspen ecosystems were excluded as discrete zones due to their broad ecological amplitude.The geo-vegetation zonation outlined in this paper is the first attempt at quantifying vegetation along with the environment at a macroclimatic level in Mongolia. This coarsescale zonation provides a framework for building a comprehensive ecological classification, a background for sustainable forest management, which is currently unavailable in Mongolia and many central Asian countries. Additionally, it offers a roadmap for a comprehensive ecosystem survey and may act as an information platform and reference for current environmental issues such as forest degradation across Mongolian landscapes.